Short Communication: Knowledge mobilization and ignorance mobilization dynamics in veterinary research - Gaudet, Joanne J.; Czub, Stefanie (Université d'Ottawa | University of Ottawa, 2012)
“[I]t is not just the unknowns that [veterinarian researchers] should be concerned about but [also] the re-emergence of what we consider to be the ‘knowns’...” (Priestnall and Smith, 2012:272). This interplay between knowledge and ignorance is the starting point to explore veterinary research using a dynamic model of knowledge and ignorance mobilization in science (Gaudet et al., 2012; Gaudet, 2012). Harnessing empirical evidence from 'The Veterinary Journal' and building on scholarship from veterinary science and sociology, the aim is to probe knowledge and ignorance dynamics through social, physical and epistemic processes at critical junctures in the model. In conclusion, Priestnall and Smith’s overt consideration of veterinary ignorance joins a convergent interest from the natural and the social sciences for ignorance dynamics.
Keywords: ignorance mobilization; knowledge mobilization; sociology of knowledge; sociology of ignorance; veterinary research; nescience; sociology of science and technology